Vender, comprar, trocar e socializar: a participação das mulheres nas feiras de Mambaí e Posse no estado de Goiás, Brasil - Lívia Aparecida Pires de Mesquita; Maria Geralda de Almeida (Confins)
The fairs that take place in the urban area of the municipalities of Mambaí and Posse, in the state of Goiás-Brazil, are important ways of commercializing the production of the settlements, and, also, affecting the lives of the settled women. In this article, it is proposed to analyze the changes in the lives and conditions of women who started to earn their own income from their work and entered the public space of the fairs that take place in those municipalities. Methodologically, theoretical and field researches were carried out with women from the Agrovila, Cynthia Peter, Mambaí, Paraná and Capim de Cheiro settlements, in the municipality of Mambaí (GO) and in the Nova Grécia settlement in the municipality of Posse (GO). Settled women’s participation in the public space and in commercial activities, as producers and marketers, influences the process of empowerment and, consequently, in the relationships established with the family and society. When leaving the private sphere and conquering her space in the public sphere, women break with the patriarchal structures, still strong in the rural space that dichotomize the spaces according to sex and naturalize the public as masculine.